Kolaborasi Produksi Konten YouTube melalui Multi-Channel Network: Studi pada Kreator Sandy SS dengan Collab Asia - Catleya Indah Lestari; Irwansyah Irwansyah (Asosiasi Pendidikan Tinggi Ilmu Komuniasi (ASPIKOM) Wilayah Riau, 2021)
Within the growth of the audio-visual digital industry, specifically on video-based social media, YouTube, requires video content creators to develop and transform themselves. This research will explain how a multi-channel network (MCN) company works and collaborates with creators to actualize an interesting content production and a worth-watching videos on YouTube. This research also will discern how a multi-channel network company helps their creators that in need to produce content and use their channel optimally. This research shows that content production collaboration using five stages of diffusion of innovations by Everett Rogers analyzes deeper on how Collab Asia as a multi-channel network company perform the collaboration to produce video content on YouTube works out well. This research shows that all five stages of diffusion of innovations from both sides, Sandy SS as content creator and Collab Asia as the multi-channel network company, goes well.